Tuturan Ritual Toit Ulan Pada Masyarakat Desa Pana Kecamatan Kolbano Kabupaten Timor Tengah Selatan - Boimau, Sanhedri; Bete, Dixon E.M. Taek (Universitas Persatuan Guru 1945 NTT, 2019)
This study aims to determine the form, function, meaning and value contained in the speech RTU in the community of Pana Village, Kolbano District, South Timor Regency. The methods and techniques for taking data used in this research are observation (involved observer), interview, recording, note-taking, and documentation. The data will be analyzed qualitatively based on cultural linguistics approach. It’s because the cultural meanings and values that contained in the RTU speech can be applied as an effort to preserve culture. Thus, the efforts of preserving the language and culture of Pana Village community can be brought up. The result in these research and discussion showing that the form of the RTU speech consists of: introduction, contents and the closing section. The functions in this RTU speech for the Pana Village community at Kolbano District, the Region of Central South Timot, are as follows: (1) Magical functions; (2) Religious functions; and (3) expressive functions. Based on those functions, the meaning contained in the RTU speech is (1) religious meaning; (2) Economic meaning; and (3) Sociological meanings. The values stated in the RTU speech are (1) Religious values; (2) Economic value; (3) Social value.